Development of Comic in Qiroah Learning Introduction Material for VII Grade at Mts Muallimin NW Pancor / Pengembangan Media Komik Pada Pembelajaran Qiroah Materi Perkenalan Kelas VII Mts Muallimin NW Pancor - Hidayat Agusvian; Asep Sopian; Nunung Nursyamsiah (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2021)
Learning the Arabic language at Mts Muallimin NW pancor using the standard textbooks without any improvisation in presenting Arabic language learning materials, the author tries to develop Arabic language learning media with comic media aimed at presenting new media that are more attractive to students Mts Muallimin NW Pancor, the methodology used in this research is the research method of development R&D ( Research and Development) Borg and Gell. One media expert lecturer and one material expert lecturer reviewed product feasibility and responded by 30 students of grade VII MTS Muallimin NW Pancor; the instrument in this research is a questionnaire to see the quality of products and students' responses media. The assessment results from both experts obtained a value of 52 for the assessment of material experts in the range of 44.16 < X_(<) 54.48, which means comic media can be said to be valid and 65 for the assessment of media experts and is in the range of 54.36 < X_(<) 67.08. It means comic media can be said to be valid. Moreover, the questionnaire's response with respondents who answered 'Yes' in the school MTS Muallimin NW Pancor was about 94.8% compared to students who answered